Design principles of microparticle size and immunomodulatory factor formulation dictate antigen-specific amelioration of multiple sclerosis in a mouse model. (March 2023) - Kwiatkowski, Alexander J.; Helm, Eric Y.; Stewart, Joshua; Leon, Juan; Drashansky, Theodore; Avram, Dorina; Keselowsky, Benjamin
Abstract: Antigen-specific therapies allow for modulation of the immune system in a disease relevant context without systemic immune suppression. These therapies are especially valuable in autoimmune diseases such as multiple sclerosis (MS), where autoreactive T cells destroy myelin sheath. This work shows that an antigen-specific dual-sized microparticle (dMP) system can effectively halt and reverse disease progression in a mouse model of MS. Current MS treatments leave patients immunocompromised, but the dMP formulation spares the immune system as mice can successfully clear a Listeria Monocytogenes infection. Furthermore, we highlight design principles for particle based immunotherapies including the importance of delivering factors specific for immune cell recruitment (GM-CSF or SDF-1), differentiation (GM-CSF or FLT3L) and suppression (TGF-β or VD3) in conjunction with disease relevant antigen, as the entire formulation is required for maximum efficacy. Lastly, the dMP scheme relies on formulating phagocytosable and non-phagocytosable MP sizes to direct payload to target either cell surface receptors or intracellular targets, as the reverse sized dMP formulation failed to reverse paralysis. We also challenge the design principles of the dMP system showing that the size of the MPs impact efficacy and that GM-CSF plays two distinct roles and that both of these must be replaced to match the primary effect of the dMP system. Overall, this work shows the versatile nature of the dMP system and expands the knowledge in particle science by emphasizing design tenets to guide the next generation of particle based immunotherapies.